To nip it or let it bloom: Life cycle assessment of lab-scale catalysts used in low-TRL CCUS technologies - Tanisha Kar; Hari Prakash Veluswamy (Sustainable Chemistry for Climate Action)
Excessive reliance on fossil fuels results in the increasing accumulation of carbon dioxide (CO2) in the atmosphere, contributing to substantial global warming. To mitigate the release of this greenhouse gas, CCUS technology integrates carbon capture, utilization, and storage, providing a comprehensive solution to address the impact of industrial activities on climate change. While numerous experimental-scale CCUS processes are being studied, there is a need to compare their environmental impacts. This paper focuses on the life cycle assessment (LCA) of lab-scale catalysts used in low technology readiness level (TRL) CCUS methodologies, employed to obtain a single target product. It includes a case study of two Cu-based catalysts for the conversion of CO2 into ethanol. Selection of ethanol as the CCU product is due to its prospects as a renewable fuel. Both grid electricity and photovoltaic-based electricity for catalyst synthesis have been used, resulting in a comparative study of four separate product systems. The two catalysts used in this assessment are Cu/C-0.4, and Cu@Na-Beta. Cu/C-0.4 catalyst has Cu nominal loading of 0.4wt%, over carbon support. Cu@Na-Beta consists of embedded 2–5 nm Cu nanoparticles in crystalline particles of Na- Beta zeolite. 17 impact categories were selected for the life cycle impact assessment (LCIA). In all categories, Cu/C-0.4 has more environmental impact than Cu@Na-Beta, indicating that it is environmentally less harmful to synthesize Cu@Na-Beta for CCU applications than Cu/C-0.4 under the studied conditions. Thus this study outlines the method of using LCA for preliminary screening of potential technologies that can be considered for commercial implementation.